The little things that run the mountain: direct and indirect role of ants in ecosystem processes in forest and grassland - Tiago Vinícius Fernandes (2022)
The last decades have witnessed a rampant acceleration of human activities, which has led, among other stressors, to an increasing loss of biodiversity and interference in biological interactions. However, we still seldom an understanding of the consequences of loosing key groups participating in ecosystem functioning. In this context, ants stand out as the planet's most abundant group of terrestrial animals. Ants are involved in several ecosystem processes, both directly by promoting scavenging of nutrients, soil bioturbation, seed dispersal and pollination; and indirectly in decomposition and herbivory by preying upon insects that perform those functions (e.g. termite and herbivorous insects). Considering the ant’s relative contribution to those processes on large scales, there are still few quantitative studies embracing it. This leaves a large gap to fill; for example, to clarify how habitat characteristics can modify ants' role in the ecosystem processes. In this study, we aim to evaluate ants' direct and indirect effects on ecosystem processes in two contrasting habitats, grassland and forest. More specifically, we assessed the direct effect of ants, non-ant invertebrates and vertebrates in scavenging Nitrogen and Carbon-rich resources (Chapter I); and measured the indirect – top-down – effects of ants on herbivory at the plant community level and decomposition by termites (Chapter 2). To do so, we run a large-scale ant suppression experiment in two contrasting natural habitats in the Brazilian mountains: grassland (campo rupestre) and forest (montane rainforest). We suppressed 70% of ants in both habitats, which impacted scavenging in the grassland by 57% and by 31% in the forest. We also showed that ant suppression can more than double herbivory at the plant community level in both habitats and double the decomposition by termites in grassland but not in the forest. We support that the higher abundance and activity in open habitats will likely increase their importance in scavenging and decomposition but not for herbivory. Finally, we highlight the irreplaceable, direct or indirect, role of ants in maintaining ecosystem functioning in undisturbed environments. Consequently, disturbances that impact ant communities, especially those caused by humans, could greatly impact ecosystem functioning.